Accumulation characteristic of nitrogen in reservoirs during the ice-covered period under superimposed influence of ice and sediments: A case study of Biliuhe reservoir. (1st November 2022) - Hu, Suduan; Wang, Tianxiang; Xu, Shiguo; Ma, Lingxiao; Wang, Tianzi; Sun, Ya
Abstract: Reservoirs located in middle and high latitudes freeze for months in winter, where the accumulation characteristics of pollutants are changed by superimposed influence of salt exclusion from ice on the surface and pollution release from sediments at the bottom. Taking total nitrogen (TN) of Biliuhe reservoir in Northeast China as an example, we developed a model to simulate TN accumulation characteristics influenced by ice and sediments during the freezing period (NACISF), and quantified contributions of TN from ice and sediments. Model parameters of ice and sediments were determined by laboratory freeze-up simulation experiment and sediment release flux simulation experiment, and water quality data were obtained from field investigations. Results showed that the annual average amount of TN input during the ice-covered period from 2015 to 2020 was 220.77 t, the output was 400.11 t, and the accumulated amount was 589.52 t. TN excluded from ice and released from sediments contributed 8.12% and 7.17% of the total TN inputs in winter, respectively. Analysis showed that the TN excluded from ice was positively correlated with ice thickness and initial TN concentration. The maximum ice thickness of Biliuhe reservoir had a 13 year cyclic feature, and the proportion of TN excluded from ice to the total TN inputs in different periods ranged from 10.68% to 17.30% (mean 13.18%). Meanwhile, TN accumulated seasonally as summer > autumn > winter > spring. The TN exclusion effect in 2050 would be weakened when considering the combined effects of climate change and human activities, with a reduction of about 40.85% compared to the current. It is concluded that the NACISF model took into account the influences of both ice and sediments, which provided a detailed understanding of the accumulation characteristics of TN during freezing period, and had important reference significance for water quality management in winter. Graphical abstract: Image 1 Highlights: A TN accumulation model considering ice and sediments was built. TN accumulated in reservoir during freezing period was calculated. Contributions of TN released from ice and sediments were separately quantified. Initial concentration and temperature control the amount of excluded TN from ice. Reservoir sediments release more N under high temperature and low oxygen.